2018
DOI: 10.1007/s10067-018-4104-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of autoimmunity and inflammation on endothelial function and thrombosis in systemic lupus erythematosus patients

Abstract: The aim of this study is to assess the relationship between autoimmunity and endothelial activation/damage (ICAM-1 and vWF serum levels) and the degree of prothrombotic activity (thrombin-antithrombin complexes-TAT serum levels) in SLE. In 60 clinically stable SLE patients, levels of the following parameters were estimated in their serum: lupus anticoagulant (LA), anticardiolipin antibodies in both IgG and IgM classes (aCL-IgG and aCL-IgM, respectively), antiβ2GPI antibodies in both IgG and IgM classes (antiβ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…1), 18 studies met the criteria for inclusion in the systematic review and meta-analysis: 6 studies investigated both F1 þ 2 and TAT, 3,12-16 7 studies investigated F1 þ 2 only, [17][18][19][20][21][22][23] and 4 investigated TAT only. [24][25][26][27] One of the studies 27 did not report the number of patients positive and negative for aPL, and at the time of submission of this article the authors had not replied to our request for such numbers. Hence, we could not include their data in the meta-analysis.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…1), 18 studies met the criteria for inclusion in the systematic review and meta-analysis: 6 studies investigated both F1 þ 2 and TAT, 3,12-16 7 studies investigated F1 þ 2 only, [17][18][19][20][21][22][23] and 4 investigated TAT only. [24][25][26][27] One of the studies 27 did not report the number of patients positive and negative for aPL, and at the time of submission of this article the authors had not replied to our request for such numbers. Hence, we could not include their data in the meta-analysis.…”
Section: Results Of the Systematic Reviewmentioning
confidence: 99%
“…Nevertheless, our overall results show that (1) several authors have used 3,[12][13][14][15][16][24][25][26] and still use TAT as a marker of coagulation activation in APS, 27 oblivious to the early studies on its invalidity 4,31 ; (2) most authors failed to report aPL titers or LA strength, relying solely on aPL positivity to categorize groups, a regrettable phenomenon that we have noticed in other meta-analyses 32,33 ; (3) none of the articles assessed a linear relationship between aPL and F1 þ 2; (4) aPL may interfere in the measurement of F1 þ 2, possibly explaining the wide heterogeneity of the pooled F1 þ 2 data between aPL þve and Àve groups and casting some uncertainty on the effect sizes; (5) relative to controls, aPL Àve SLE patients are in a state of coagulation activation.…”
Section: Discussionmentioning
confidence: 97%
“…3 ). Several previous reports have described linkages between autoimmunity and atherosclerosis in other disease populations and animal models ( 32 34 ). Nonetheless, to our knowledge, this is the first study that has identified an Ag-specific adaptive immune response in COPD patients that is associated with atherosclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…Among autoimmune diseases in general, systemic lupus erythematosus (SLE) is characterised by a loss of tolerance to self-antigens and the production of high titres of serum autoantibodies [1]. Inflammation processes in SLE result in the increase in inflammatory mediators that promote accelerated atherosclerosis, endothelium damage, and SLE progression [2].…”
Section: Introductionmentioning
confidence: 99%